Differences in Balance Function Between Cancer Survivors and Healthy Subjects: A Pilot Study. (December 2018) - Morishita, Shinichiro; Mitobe, Yuta; Tsubaki, Atsuhiro; Aoki, Osamu; Fu, Jack B.; Onishi, Hideaki; Tsuji, Tetsuya
Older adults who have survived cancer experience significantly more falls compared with healthy adults. Adult cancer survivors may also have a lower balance function than healthy adults. We examined muscle strength and balance function among 19 cancer survivors and 14 healthy subjects. The mean age of the cancer survivors was 51.5 ± 11.2 years; 6 men and 13 women. Cancer diagnoses included breast cancer, retroperitoneal sarcoma, acute leukemia, lung cancer, colorectal cancer, thyroid cancer, Ewing's sarcoma, and tongue cancer. The mean age of healthy subjects was 47.4 ± 14 years; 3 men, 11 women. Muscle strength was assessed using hand grip and knee extensor strength tests. Balance function was evaluated using the Timed Up and Go (TUG) test, and body sway was tested using a force platform. No significant differences were found with respect to right and left grip strength or right and left knee extension strength between the 2 groups. A significantly higher TUG time was observed in cancer survivors than in healthy subjects ( P < .05). With eyes open, the area of the center of pressure was significantly larger in cancer survivors than in healthy subjects ( P < .05). Similarly, the length per area was significantly lower both with eyes open and closed for cancer survivors than for healthy subjects ( P < .05). TUG was significantly correlated with muscle strength in both groups ( P < .05). However, no body sway parameters were related to muscle strength in either group. Cancer survivors had lower balance function that might not have been related to muscle strength. Cancer survivors should be evaluated for balance function as there is a potential for impairment. The findings of this study will be relevant for planning the prevention of falls for cancer survivors.